Adhesive Coacervates Driven by Hydrogen‐Bonding Interaction. Issue 43 (2nd October 2020) - Peng, Qiongyao; Chen, Jingsi; Zeng, Zicheng; Wang, Tao; Xiang, Li; Peng, Xuwen; Liu, Jifang; Zeng, Hongbo
Abstract: Coacervation plays a critical role in numerous biological activities such as constructing biological tissues and achieving robust wet adhesion of marine sessile organisms, which conventionally occurs when oppositely charged polyelectrolytes are mixed in aqueous solutions driven by electrostatic attraction. Here, a novel type of adhesive coacervate is reported, driven by hydrogen‐bonding interactions, readily formed by mixing silicotungstic acid and nonionic polyethylene glycol in water, providing a new approach for developing coacervates from nonionic systems. The as‐prepared coacervate is easily paintable underwater, show strong wet adhesion to diverse substrates, and has been successfully applied as a hemostatic agent to treat organ injuries without displaying hemolytic activity, while with inherent antimicrobial properties thus avoiding inflammations and infections due to microorganism accumulation. This work demonstrates that coacervation can occur in salt‐free environments via non‐electrostatic interactions, providing a new platform for engineering multifunctional coacervate materials as tissue glues, wound dressings and membrane‐free cell systems. Abstract : Adhesive coacervates are acquired by a facile mixing of silicotungstic acid and nonionic polyethylene glycol aqueous solutions followed by liquid–liquid separation, which is driven by hydrogen‐bonding interactions. The as‐prepared coacervate exhibits underwater paintability, antimicrobial property, as well as strong and reversible wet adhesion, enabling the coacervate to be used as hemostatic tissue adhesives.